COMPARISON OF THE MEAN POST OPERATIVE PAIN AFTER MANUAL AND ROTARY INSTRUMENTATION FOR ROOT CANAL TREATMENT OF SINGLE ROOTED TEETH WITH IRREVERSIBLE PULPITIS - Nida Gul Sepah,; Qureshi, Asim; Imran khattak,; Muhammad Izaz Ali,; Azhar Iqbal,; Mahnoor Iqbal, (Journal of Ayub Medical College Abbottabad, 2024)
Background: The rotary instruments are becoming a more common choice for both general dentists and endodontists. Trials are being conducted to assess their potential benefits, especially on post-operative pain. Therefore, the present study is aimed at recording the intensity of pain experienced by the patients after root canal procedure through `a rotary file system (Hyflex CM™) and comparing it with older techniques such as manual hand files (K-files) which are more commonly used. Methods: The current randomized clinical trial was conducted on 60 patients diagnosed with irreversible pulpitis. A patient who had taken an analgesic in the past 12 hours was excluded. A visual analogue scale (VAS) was used for recording the patient’s pain readings. In the two intervention groups, rotary file systems and conventional manual K files were used for cleaning and shaping. Results: Pain readings in the two types of instrumentation techniques showed that there was a decrease in the pain level in both groups from the initial pain level. When comparing the two groups at different post-operative intervals (6hr,12hr,48hrs, and 1 week) it was found that there was statistically significantly less pain in the rotary group. (p values <0.05). Conclusion: The current study concludes that there was a significant difference in post-operative pain between manual and rotary Hyflex™ after the first visit of root canal therapy.